2015
DOI: 10.1186/s12885-015-1082-7
|View full text |Cite
|
Sign up to set email alerts
|

Local control in metastatic neuroblastoma in children over 1 year of age

Abstract: BackgroundLocal control is always considered in metastatic neuroblastoma (NBL). The aim of this study is to evaluate the impact of radical surgery on survival in children over 1 year of age.MethodsFifty-eight patients older than 1 year of age with metastatic NBL were treated with conventional plus high-dose chemotherapy with or without addition of local radiotherapy (RT, 21Gy). Surgery was classified as radical surgery (complete resection and gross total resection) or non-radical surgery. The Kaplan-Meier meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…34,35 In fact, omission of radiation in patients with HR-NB who have undergone GTR has resulted in favorable local control rates in some studies 27,36 but not all. 3,37 Although there has been a decrease in life-threatening late effects with reduction in treatment exposure seen with childhood cancers such as Wilms and leukemia, there has been an increase in late mortality in neuroblastoma, attributed to the increase in therapeutic exposure. 38 With the primary goal of balancing outcomes with toxicity, and with the favorable rates of local control observed in our large cohort, we recommend dose reduction on protocol in patients with favorable prognostic factors, such as those who achieve GTR and do not have adverse biologic factors like MYCN amplification or LDH ≥1500 U/L.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In fact, omission of radiation in patients with HR-NB who have undergone GTR has resulted in favorable local control rates in some studies 27,36 but not all. 3,37 Although there has been a decrease in life-threatening late effects with reduction in treatment exposure seen with childhood cancers such as Wilms and leukemia, there has been an increase in late mortality in neuroblastoma, attributed to the increase in therapeutic exposure. 38 With the primary goal of balancing outcomes with toxicity, and with the favorable rates of local control observed in our large cohort, we recommend dose reduction on protocol in patients with favorable prognostic factors, such as those who achieve GTR and do not have adverse biologic factors like MYCN amplification or LDH ≥1500 U/L.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with Tajiri et al ., who reported that extirpation of the primary tumor without extensive surgery, similar to GTR/STR, might prevent local recurrence when combined radiation therapy is used for INSS 4 NB patients who have undergone radical operation after induction chemotherapy. Moreover, radical surgery did not contribute to improve OS in patients with metastatic NB, despite the fact that the patients underwent surgery immediately after conventional chemotherapy …”
Section: Discussionmentioning
confidence: 94%
“…Moreover, radical surgery did not contribute to improve OS in patients with metastatic NB, despite the fact that the patients underwent surgery immediately after conventional chemotherapy. 13 In the 1980s, the conventional treatment strategy (i.e. 30 Gy irradiation without HDC), was shown to improve prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tomotherapy, Volumetric-modulated arc therapy, Neuroblastoma, Dosimetric comparison, Pediatric high-risk forms of the disease. [1][2][3] Radiotherapy constitutes a complex problem because of the shapes of the target volumes and the need to minimize the involvement of organs at risk (OARs). 4 In recent years, new radiotherapy technologies, such as volumetric-modulated arc therapy (VMAT) and helical tomotherapy (TOMO), have been widely used in the clinic.…”
Section: Introductionmentioning
confidence: 99%